Broadband Microspectrophotometer with Tablet PC Control - Weng, Chun-Jen; Hsu, Ken-Yuh; Chen, Yung-Fu; Chang, Shian-Wen; Cho, Wen-Hao; Chen, Fong-Zhi (My University, 2012)
This study investigated the design, fabrication, and performance characterizations of a broadband microspectrophotometer with tablet PC wireless control. The microspectrophotometer system performed rapid measurements, was highly accurate, and was easy to operate. The calibrations for two measurement modes for transmittance and reflectance spectra were performed with bulk and multilayer thin-film samples. Objective lenses with various magnifications were introduced to verify the possibility of microscopic spectra measurements in the system. A polarization identification capability was also included in the system.
Keywords: microscopic; microspectrophotometer; reflectance; tablet PC; spectrum; supercontinuum light source; transmittance